Papaya pulp for enzymatic wound debridement in burns - Rajshree C Jayarajan; Puthucode V Narayanan; Hirji S Adenwalla (Wolters Kluwer Medknow Publications, 2016)
Context: Early surgical debridement in burns has its disadvantages like extensive blood loss and long anaesthesia time and risks. Enzymatic wound debridement as an alternative to surgical debridement has been assessed for its effectiveness, safety and patient compliance. Aims: To assess the effectiveness and safety of papaya pulp as an enzymatic wound debriding agent in burns. Setting and Design: The study was conducted including 50 patients with second degree and third degree burns, age ranging from 15 to 60 years from January 2004 to December 2004 at the Burns Centre, Department of Plastic, Reconstructive and Burns Surgery, Jubilee Mission Medical College and Research Institute, Thrissur, Kerala, India. Materials and Methods: A prospective study including 50 patients with second degree and third degree burns, age ranging from 15 to 60 years was carried out from January 2004 to December 2004 at the Burns Centre, Department of Plastic, Reconstructive and Burns Surgery, Jubilee Mission Medical College and Research Institute, Thrissur, Kerala, India. There were 38 female and 12 male patients in the study group. Areas of burns ranging from 10% to 60% TBSA were included in the study. Daily dressings were done using autoclaved unripe papaya pulp smeared on potato peel dressing. The progress was assessed daily and application stopped when adequate debridement has been achieved or a maximum of 1 week. Statistical Analysis Used: None. Results: All 50 patients included initially completed the study. There were 38 females and 12 males. Papaya pulp was found to be a very effective debriding agent in all cases. Deep dermal wounds cleared up in 5 to 6 days and eschar in full thickness burns became loose by this period so that it needed minimal surgical debridement. The granulation tissue found following debridement with papaya pulp was pink and healthy. In patients who had to be taken up for grafting, a mild scraping was sufficient before placement of a graft. This has helped on reducing blood transfusions and has considerably reduced anaesthesia time. Conclusions: The use of papaya pulp results in 1. Early and complete non-invasive debridement, 2. Healthy granulation tissue, 3. Decreased blood loss and hence decreased number of blood transfusions in cases which have to be grafted, as excision is avoided. 4. Less operating time and hence less anaesthesia time.